Case report of a medication error: In the eye of the beholder. Issue 28 (July 2016) - Naunton, Mark; Nor, Kowsar; Bartholomaeus, Andrew; Thomas, Jackson; Kosari, Sam
Abstract: Introduction: The World Health Organisation recognizes confusing drug names as one of the most common causes of medication errors. Other factors include spelling, phonetic, or packaging similarities. Case presentation: We presented a case report of an inadvertent administration of a non-ocular pharmaceutical product (Novasone ® lotion) into the eye of an octogenarian individual, and briefly reviewed the relevant literature. Discussion: We discussed prevention strategies to avoid similar ophthalmic medication errors.